(untitled) (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2017)
This article is made in the framework of the investigation “Gender, access rights and policies in the Province of La Pampa, from law 26485” and its main objective is to explore various aspects of enforcement 26150 on Comprehensive Sexuality Education (hereinafter ESI) and Law 26485 in the Province of La Pampa. First, a brief reference to the project that frames this proposal is made, then the most important international, national and local regulations on the issue and possible links between the two laws is reviewed. In a third stage, conceptual issues of ESI and its relationship with public policies to prevent violence against women are addressed.